2014
DOI: 10.1038/nm.3517
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil granulocytes recruited upon translocation of intestinal bacteria enhance graft-versus-host disease via tissue damage

Abstract: Acute graft-versus-host disease (GVHD) considerably limits wider usage of allogeneic hematopoietic cell transplantation (allo-HCT). Antigen-presenting cells and T cells are populations customarily associated with GVHD pathogenesis. Of note, neutrophils are the largest human white blood cell population. The cells cleave chemokines and produce reactive oxygen species, thereby promoting T cell activation. Therefore, during an allogeneic immune response, neutrophils could amplify tissue damage caused by conditioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
196
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(217 citation statements)
references
References 43 publications
16
196
0
5
Order By: Relevance
“…In particular, cell-cell interactions mediated by OX40, CD58, CD59, and their ligands have been proposed (12,31). Alternatively, a role for ROS release has also been suggested (42). Our data suggest that CD11a/CD54 interaction powerfully contributes to the elicitation of the costimulatory effects of neutrophils on CD8þ T-cell activation.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In particular, cell-cell interactions mediated by OX40, CD58, CD59, and their ligands have been proposed (12,31). Alternatively, a role for ROS release has also been suggested (42). Our data suggest that CD11a/CD54 interaction powerfully contributes to the elicitation of the costimulatory effects of neutrophils on CD8þ T-cell activation.…”
Section: Discussionmentioning
confidence: 61%
“…Neutrophil-CD8 þ Tcell interactions might indeed be operational in a wider range of conditions, thus supporting the notion of a highly effective cooperation between innate and adaptive immune responses. Remarkably, similar results have also emerged from studies conducted in experimental models (42) and in clinical settings, including early-stage lung cancer (12,13) and autoimmune and infectious disease (31). Underlying molecular mechanisms have not been fully clarified.…”
Section: Discussionmentioning
confidence: 75%
“…It remains to be shown how mast cells and neutrophils are activated by contact allergens. Also, PRRs may play a role here as recently demonstrated for TLR-dependent neutrophil activation in graft-versus-host disease [25]. Interestingly, a recent study revealed that neutrophils leave chemokine cues for T cell migration in the airways.…”
Section: The Innate Cellular Immune Response To Contact Allergensmentioning
confidence: 73%
“…) and peroxynitrite were also interact with ROS, and all of these species were known as RONS which is produced by immune system [57] but excessive production of RONS would damaged almost all classes of biomolecules, such as lipids [58] proteins [59] and DNA. [60,61] The term "oxidative stress" was introduced in 1970s and 1980s to describe these deleterious processes.…”
Section: Oxidative Stressmentioning
confidence: 99%